PENINGKATAN HASIL BELAJAR LUAS TRAPESIUM DAN LAYANG-LAYANG MENGGUNAKAN MODEL PEMBELAJARAN TAI DI SEKOLAH DASAR - Murniati, Murniati; Ahmad, Syafri; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research was done due to the fact that teachers dominated the learning process and still used the conventional approach in the learning process. The design of the research was class action research using both qualitative and quantitative approaches.The subjects of the research were the teacher and twenty five grade student of that consisted of 14 boys and 11 girls. The result of the lesson plan analysis in cycle I was 75% and in cycle II was 89,06 %. Students’ learning outcome in cycle I was 73,59% and it increased in cycle II to 82,59 % Thus, the team assisted individualization model successfully improved students’ trapezoids and kites leaning outcomesKeywords: Trapezoids and Kites learning Outcomes, the Team Assisted Individualization Model